Problems in models of opening networks resources and methods for calculating system performance and reliability - Gulnara B.; Ahmad A.R.B.; Ismail R. (IEEE Computer Society, 2023)
Reliability; Distributed computing systems; Geographical locations; Grid resource discovery; Heterogeneous platforms; Performance and reliabilities; Performance computing; Resource discovery; Resource provisioning; Grid computing